The Influence of Fishing Assets and Migration Time to Catch Squid Fisheries on Seasons Variability - Dewi Susiloningtyas; Mennopatria Boer; Luky Adrianto; Fredinand Julianto (Faculty of Geography, Universitas Gadjah Mada, 2014)
This paper was based on primary data from Lombok squid fishermen communities. The presence of fishermanmigrants in fishing activities at salura island is very important for their livelihood. The purpose of this study wasdetermined the catch in different season influenced by the duration time of migration and fishing assets. Fishing assetsdescribed of number of fishing gear, number of boat, and number of engine. Duration time described are length of stayat located of migration and frequency of migration. Data were analyzed by regression statistic analysis. The results is thatfishing assets of fishing gear have influenced to cacth both on east monsoon and west monsoon season. Then lengthof stay at the destination of migration affect the catch too, when the squid are abundant in the east monsoon season.